Alternativa à tecnologia de fornecimento de vapor e eletricidade em destilarias de etanol de cana para projetos green field via biogás de bagaço, vinhaça e torta de filtro - Fernandes, Matheus Menezes (Universidade Federal de São Carlos, 2023)
Considering the great relevance and impact that the sugar and alcohol sector has in the national context, with a focus on waste generation and the cogeneration process, it is essential to study technologies that can offer alternatives to the treatment and disposal of this waste. An alternative route was proposed for the cogeneration of thermal and electrical energy in ethanol distilleries, a route that uses the main residues of the process (bagasse, straw, filter cake and vinasse) to produce biogas, which will be used as fuel for the cogeneration system using an internal combustion engine or gas turbine in a first stage and a heat recovery boiler (HRSG) in a second stage. In addition to being used in cogeneration, biogas can go through a purification process, transforming it into biomethane and replacing the diesel oil consumed by machines and trucks used for planting, harvesting and transport. To simulate this technological route, several process parameters and assumptions were adopted that allowed the calculations to be carried out. An economic feasibility analysis of the technology was also carried out, using cost and revenue assumptions, in addition to financial indicators such as Net Present Value (NPV) and Internal Rate of Return (IRR). Several different scenarios and combinations were simulated for the generation of biogas from filter cake, vinasse and also from bagasse and straw to supply the fleet and cogeneration. Supplying the fleet with biomethane produced from biogas is the most financially attractive option. The best results were obtained with the use of 100% of the filter cake and 15% of the vinasse for the production of biomethane capable of supplying the entire diesel demand of the automotive fleet. The alternative cogeneration technology is also attractive (considering technical and environmental aspects), but due to the importation of equipment, investment is high, reducing its competitiveness, although there is a greater export of electricity.
Alternative technology for supplying steam and electricity in sugarcane ethanol distilleries for green field projects via biogas from bagasse, vinasse and filter cake
Keywords: Destilaria; Etanol; Cogeração; Bagaço; Palhiço; Vinhaça; Biogás; Biometano; Distillery; Ethanol; Cogeneration; Bagasse; Straw; Vinasse; Biogas; Biomethane; ENGENHARIAS::ENGENHARIA QUIMICA